2015
DOI: 10.1016/j.jceh.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Hepatic Encephalopathy and Brain Edema in Acute Liver Failure

Abstract: Neuropathologic investigations in acute liver failure (ALF) reveal significant alterations to neuroglia consisting of swelling of astrocytes leading to cytotoxic brain edema and intracranial hypertension as well as activation of microglia indicative of a central neuroinflammatory response. Increased arterial ammonia concentrations in patients with ALF are predictors of patients at risk for the development of brain herniation. Molecular and spectroscopic techniques in ALF reveal alterations in expression of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 69 publications
4
79
0
Order By: Relevance
“…Liver-brain proinflammatory signaling mechanisms involve the transduction of systemically derived cytokines as well as the gliotoxic effects of ammonia and lactate [53].…”
Section: Cerebral Edema and Intracranial Hypertensionmentioning
confidence: 99%
“…Liver-brain proinflammatory signaling mechanisms involve the transduction of systemically derived cytokines as well as the gliotoxic effects of ammonia and lactate [53].…”
Section: Cerebral Edema and Intracranial Hypertensionmentioning
confidence: 99%
“…The blood-brain barrier permeability is not grossly altered. [15][16][17] Glutamine levels in the brain are significantly increased in patients with ALF. Previously, these levels were not found to correlate with the severity of encephalopathy or presence of cerebral edema.…”
Section: Correct Answers: D and Ementioning
confidence: 99%
“…Previously, these levels were not found to correlate with the severity of encephalopathy or presence of cerebral edema. 15,18,19 However, a recent study has shown a progressive increase in glutamine and glutamate peak on magnetic resonance spectroscopy with the increase in severity of HE. 20 …”
Section: Correct Answers: D and Ementioning
confidence: 99%